Hypoglycemic Property of the Ethanolic Extract of Cinnamon on Alloxan Induced Diabetic Mice (Bangladesh Medical Journal, 2014)
This study aimed to investigate the effect of ethanolic extract of cinnamon on hyperglycemic mice. Cinnamon extract was administered at 150mg/kg and 200mg/kg body weight in alloxan induced hyperglycemic mice and the glucose lowering effect was compared to a standard oral anti diabetic drug- glibenclamide for 28 days. The fasting glucose level was measured in serum of normal and alloxan induced hyperglycemic mice. Diabetic mice exhibited an increase in the levels of glucose. It was found that blood glucose concentration was significantly decreased in a dose-dependent manner (p